Case Report: Type 2 Diabetes Mellitus for The Elderly with Less Family Support - Fitria Saftarina (Faculty of Medicine, Public Health, and Nursing, 2021)
Mrs. R, 65 years old came to Puskesmas B with complaints of fatigue during activities accompanied by weakness since 1 week ago. The patient has been diagnosed with Diabetes Mellitus since 2 years ago, but the patient admitted that she sometimes went to the health center once every 2 or 3 months depending on her complaints. According to the patient's acknowledgment, initially complaints of fatigue were felt rarely but gradually became more frequent and appeared during light activities and felt continuously. Complaints are not accompanied by blurred vision or numbness.The patient admitted that if the medicine from the Puskesmas ran out, complaints in the form of frequent thirst, frequent urination, hunger, and fatigue were felt again which indicated that the patient's blood sugar was rising, and the patient admitted that the highest blood sugar reached 600 mg/dL. During Mrs. R's treatment, she not only went to the health center for treatment but also frequently went to midwives and paramedics near the house.Mrs. R took the drugs metformin and glimepiride if she had just gone to a health professional when she had a complaint. Additionally, Mrs. R admitted that because of the complaint of feeling weak, Mrs. R often consumed date juice 3 X 1 spoon every day. Mrs. R is often given explanations by health workers to maintain her diet, but according to her she still cannot regulate her diet properly. Mrs. R still can be active and currently the patient is active as a housewife. Every Saturday, Mrs. R follows the exercise program from the village, namely elderly gymnastics, while on other days Mrs. R does not do sports, and only does home activities. Mrs. R denied smoking history, denied drinking alcohol, and denied taking drugs. Mrs. R currently lives with her husband and one grandson.